The Africa we want or the Africa we were given? Interrogating the African economic community and the challenges of monetary integration in West Africa - Iloh, Emeka C.; Osimen, Goddy Uwa; Okafor, Uzodinma Chukwuemeka (Journal of Contemporary International Relations and Diplomacy, 2022)
The study interrogates the possibility of achieving monetary integration in West Africa as part of efforts at realizing the envisaged African Economic Community (AEC). Eight regional economic communities (RECs) were recognized by the African Union (AU) as building blocks for the AEC, whose ultimate goal is the establishment of an economic and monetary union in Africa. These RECs are the institutional mechanisms through which this integration will be achieved, and monetary cooperation in the RECs is one of the steps towards achieving the integration. The Economic Community of West African States (ECOWAS) is one of these RECs. Extant literature accounts blame the failure to achieve monetary integration in the sub-region on the countries’ inability to meet the ‘convergence criteria’ required to establish a monetary union. This study acknowledges this but contends that though this undermines monetary integration in the continent and sub-region, much attention has not been given to the impacts of colonial legacy. The study is anchored on the theory of the post-colonial state and utilizes the documentary method of data collection. The findings indicate that the nature and character of the continent handed over to Africans at independence, especially by France, and its continued meddlesomeness, have made it very difficult for West African countries to forge a common front in monetary integration. This casts doubts on the possibility of realizing the monetary integration agenda of the AEC. The study, therefore, concludes that as long as France continues to meddle in the affairs of its former colonies in West Africa, efforts at monetary integration in the sub-region and the wider AEC are likely to continue to be undermined.